THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND ABILITY IN ARRANGING NARRATIVE PARAGRAPHS AT SMA SWASTA SANTO PETRUS MEDAN - Ginting, Indri Kristine br; Saragih, Erikson; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
This study attempts to investigate the correlation between students‟ vocabulary mastery and ability in arranging narrative paragraphs. The research approach was quantitative. The research method was descriptive. The research design of this study was a correlational design. The population of this study was second grade students of SMA Swasta Santo Petrus Medan totaling to 118 of three parallel classes. The sample of this research was the class XI MIA totaling to 38 students. The instrument of collecting the data were vocabulary test and arranging narrative paragraphs test and split half formula was used to obtain the reliability of the test. The data was analyzed by using Pearson Product Moment formula. From this study it was found that robserved is higher than rtable (0.881>0.413). It means that null hypothesis is rejected and Alternative hypothesis is accepted. As the conclusion, there is very strong correlation between students‟ vocabulary mastery and ability in arranging narrative paragraphs at SMA Swasta Santo Petrus Medan in Academic Year of 2016/2017.